Electrophysiological markers predicting impeding AV‐block during ablation of atrioventricular nodal reentry tachycardia. Issue 1 (28th December 2017) - Fragakis, Nikolaos; Krexi, Lydia; Kyriakou, Panagiota; Sotiriadou, Melani; Lazaridis, Charalambos; Karamanolis, Athanasios; Dalampyras, Panagiotis; Tsakiroglou, Stelios; Skeberis, Vassilios; Tsalikakis, Dimitrios; Vassilikos, Vassilios
Abstract: Background: Radiofrequency (RF) ablation of the slow pathway (SP) in atrioventricular nodal reentry tachycardia (AVNRT) is occasionally complicated with atrioventricular block (AVB) often predicted by junctional beats (JB) with loss of ventriculo‐atrial (VA) conduction. Methods: We analyzed retrospectively 153 patients undergoing ablation of SP for typical AVNRT. Patients were divided into two age groups: 127 ≤ 70 years and 26 > 70 years. We analyzed the interval between the atrial electrogram in the His‐bundle position and the distal ablation catheter [A(H)‐A(RFd)] and between the distal ablation catheter and the proximal coronary sinus catheter [A(RFd)‐A(CS)] before RF applications with and without JB. We evaluated if these intervals can be used as predictors of JB incidence and also of JB with loss of VA conduction. We also assessed if age influences the risk of loss of VA conduction. Results: The A(H)‐A(RFd) and A(RFd)‐A(CS) intervals were significantly shorter in RF applications causing JB than those without JB (33 ± 11 ms vs 39 ± 9 ms, P < 0.001, 14 ± 9 ms vs 20 ± 7 ms, P < 0.001, respectively). The A(H)‐A(RFd) and A(RFd)‐A(CS) intervals were also significantly shorter in RFs causing JB with VA block than those with VA conduction (29 ± 11 ms vs 35 ± 11 ms, P < 0.001, 8 ± 8 ms vs 17 ± 8 ms, P < 0.001, respectively). Patients > 70 years had shorter intervals (36 ± 11 ms vs 29 ± 8 ms, P = 0.012, 17 ± 8 ms vs 13 ± 7 ms, P = 0.027, respectively), while VA block was more common in this age group. Conclusions: The A(H)‐A(RFd) and A(RFd)‐A(CS) intervals can be used as markers for predicting JB occurrence as well as impending AVB. JB with loss of VA conduction occur more often in older patients possibly due to a higher position of SP.